2017
DOI: 10.1039/c6dt04213a
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing the active species in an aluminium-based Lewis acid system for catalytic Diels–Alder cycloadditions

Abstract: Several Al-based complexes supported by a bis(imino)aryl NCN pincer ligand have been prepared. Systematic structural and experimental evidence identified a cationic species, supported by a THF molecule, as the best Lewis acid precatalyst for a range of Diels-Alder cycloadditions. This highlighted the importance of fully isolating and characterizing the active species in any catalytic process especially when Lewis acids are used due to the presence of hidden Brønsted acids (HBAs). Finally, the control experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…After identifying the proficiency of aluminum‐ based catalysts in catalyzing arduous Diels‐Alder cycloadditions, ligand contribution on overall catalytic activity was studied. Some Al‐based complexes supported by a bis(imino)aryl NCN pincer ligand L (L=2,6‐(DipNC) 2 ‐C 6 H 3 , Dip=2,6‐iPr 2 ‐C 6 H 3 ) were synthesized and characterized . A cationic species was revealed as the most significant pre‐catalyst for the examined Diels‐Alder reaction.…”
Section: Cycloaddition Reactions As a Main Tool For Developing Sustaimentioning
confidence: 99%
“…After identifying the proficiency of aluminum‐ based catalysts in catalyzing arduous Diels‐Alder cycloadditions, ligand contribution on overall catalytic activity was studied. Some Al‐based complexes supported by a bis(imino)aryl NCN pincer ligand L (L=2,6‐(DipNC) 2 ‐C 6 H 3 , Dip=2,6‐iPr 2 ‐C 6 H 3 ) were synthesized and characterized . A cationic species was revealed as the most significant pre‐catalyst for the examined Diels‐Alder reaction.…”
Section: Cycloaddition Reactions As a Main Tool For Developing Sustaimentioning
confidence: 99%
“…[1,2] Due to the nucleophilic properties of hydrocarbyl ligandsi na ddition to their sensitivity to moisture anda ir,t he application of organoaluminum compoundsa sc atalysts is challenging. Although Uhl reported that phosphine-substituted alkenylaluminums act as frustrated Lewis pair catalysts [6] and Vidović synthesized and employedo rganoaluminum complexes supportedb yabis(imi-no)aryl NCN pincerl igand, [7] the scope of applicable catalytic reactions was narrow ( Figure 1B,U hl's and Vidović's works). We therefore chose to adopt the 2-oxazolinylphenyl (Pheox) and 2,6-bis(oxazolinyl)phenyl (Phebox) ligands, [8,9] as they can enhancet he stability of complexes and tune the Lewis acidity by the intramolecular coordination of oxazoline moieties.…”
mentioning
confidence: 99%
“…Selected bond lengths (Å) and angles (°); 7 2+ : P1-C1 1.879 (14); P1-O1 1.456 (10); P1-O2 1.711 (11); O1-P1-N1 112.6 (7); Table 1. Reported calculated first (PA 1 ) and second (PA 2 ) proton affinities and NBO partial charges at the central carbon atom q(C) of selected N-heterocyclic and carbodiphosphorane compounds in kcal/mol [114e] 3. 31 P NMR shifts (δ P in ppm) obtained for the isolated monocations of the formula [R" 2 NP(C(Ph 2 R') 2 Cl] + . Substituent combinations that were not synthetically attempted are denoted with a dash "-".…”
Section: Table Of Figuresmentioning
confidence: 99%
“…vi Summary Herein presented work expands on the recently reported synthesis and reactivity of the two-coordinate P(III)-containing dication [((Ph 3 P) 2 C)P(N i Pr 2 )] 2+ (3c 2+ ), and its two analogues [((RPh 2 P) 2 C)P(NR′ 2 )] 2+ (3d 2+ , R = Ph, R′ = Cy; 3e 2+ , R = 1/2 (CH 2 ) 3 , R′ = i Pr;). Solution and solid-state 31 P NMR isotropic shifts for the dication class were observed at ~360 ppm. Except for [3c][SbF 6 ] 2 , the 31 P CP/MAS NMR spectra reveal a high degree of structural disorder around the dicationic site in the solid state.…”
mentioning
confidence: 99%
See 1 more Smart Citation